Patient-Controlled Oral Analgesia for Postoperative Pain Management Following Total Knee Replacement - Patti Kastanias; Sue Gowans; Paul S Tumber; Kianda Snaith; Sandra Robinson (Pain Research and Management)
PURPOSE: To investigate whether patient-controlled oral analgesia (PCOA) used by individuals receiving a total knee replacement could reduce pain, increase patient satisfaction, reduce opioid use and/or reduce opioid side effects when compared with traditional nurse (RN)-administered oral analgesia.